The effect of Te-based lead-free glass powder containing Ge and Ag+ on the contact formation and electrical performance of silicon solar cells - Yu, Xianglei; Li, Wei; Sun, Hu; Qian, Zhuo; Li, Junpeng; Yu, Yang; Gan, Guoyou (Frontiers in Materials, 2024)
The Te-based glass powder exhibits distinctive characteristics such as a low melting temperature and high chemical stability, rendering it a focal point of research in the realm of glass powder applications for solar cells. In this investigation, a pioneering Ge-containing Te-based lead-free glass powder was synthesized, and the influence of GeO2 content on critical parameters such as glass transition temperature (Tg), high-temperature fluidity, high-temperature wettability, acid and alkali resistance, as well as the network structure of the glass, was systematically explored. At an optimal GeO2 content of 8%, the glass powder displayed the lowest Tg (437°C), accompanied by a subdued crystallization reaction. The high-temperature fluidity and wettability exhibited favorable characteristics, indicating that the inclusion of GeO2 in the glass powder resulted in an enhanced interface contact. Building upon this foundation, techniques to augment the Ag + content within the glass powder were investigated, along with the interaction between Ag + and the SiNx anti-reflection layer or silicon on the surface of crystalline silicon solar cells. It was discerned that the Ag + content in the glass powder significantly influences the deposition of silver microcrystals on the surface of crystalline silicon, thereby impacting the contact resistance of the solar cell. Then influences the series resistance and photoelectric conversion efficiency of the solar cell.